The Gambia : 2017 Article IV Consultation and First Review Under and Extension of the Staff-Monitored Program with The Gambia-Press Release; Staff Report; and Statement by the Executive Director for The Gambia. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that The Gambian economy has started to recover, following the sharp growth slowdown in 2016. For 2017, economic growth is estimated at 3.5 percent with a better agricultural season and a strong rebound of tourism and trade. With much-improved fiscal discipline and external financial support, the Dalasi has remained stable since April and gross international reserves increased from 1.6 months of import cover at end-2016 to 2.9 months at end-2017. Over the medium term, The Gambia can achieve a more robust growth path. This will require continued strong policy implementation and effective fiscal reforms, including ensuring debt sustainability.